PENILAIAN PENGUNJUNG TERHADAP AKSESIBILITAS KE TAMAN NASIONAL TESSO NILO KABUPATEN PELALAWAN - Mella Adelia Wati; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Tourism has become a trend of modern human life, because this human activity has a broad dimension, not just to fulfill the need for fun to enjoy the trip, but this activity gives rise to a lot of artistic and cultural economic activity. Indonesia is one of the countries that has many interesting tourist destinations to visit. Pelalawan Regency has many tourism places that have great opportunities to develop rapidly, one of them is Tesso Nilo National Park with that the author takes the title of visitor’s assessment of accessibility to Tesso Nilo National Park, Pelalawan Regency which aims to determine the assessment of visitors who visit Tesso Nilo National Park and to find out the management’s efforts to improve accessibility to Tesso Nilo National Park, the researchers use Warpani theory (2002), which says that accessibility is defined as the level of ability to achieve or obtain the goods and services needed so that accessibility can be interpreted as the degree of ease achieved by people, to objects, services or the environment. This research was carried out for four months starting from April to July 2021. This research is a mixed methods research, the data collection technique uses observation, questionnaire, interview and documentation technique. Samples from the research are visitors and managers. The results of this recapitulation show that overall the respondents gave a not good assessment of accessibility to Tesso Nilo National Park and management’s efforts to improve accessibility are still in the planning stage.Keywords : Assessment, Visitors, Accessibility and National Park